1976
DOI: 10.1017/s002531540002066x
|View full text |Cite
|
Sign up to set email alerts
|

Check-list of British marine algae-third revision

Abstract: The Preliminary Check-list of British Marine Algae (Parke, 1953), with three subsequent lists of additions and corrections (Parke, 1956,1957,1959), was superseded by the Revised Check-list of British Marine Algae (Parke & Dixon, 1964) and the Check-list of British Marine Algae - Second Revision (Parke & Dixon, 1968). Since the publication of the 1968 list, changes, both taxonomic and systematic, have been sufficiently numerous to warrant the present list incorporating further additions, corrections and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0
10

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(143 citation statements)
references
References 234 publications
1
132
0
10
Order By: Relevance
“…If it were at 13 °C August isotherm (a growth and/or reproduction limit) then H. equisetifolius would be expected in the North Sea south to the 13 °C August isotherm. In Ardr~ (1970Ardr~ ( , 1971, Dangeexd (1949), Donze (1968), Feldmann (1954, Gayral (1958), Giaccone & Longo (1976), Guiry (1978), den Hartog (1959), van den Hoek (1982a), van den Hoek & Donze (1966, 1967, Lawson & John (1977), Meunier (1965), Newton (1931), Norton (1970), Norton & Powel] (1979), Parke & Dixon (1976), Perez-Cirera (1975a), Prud'homme van Reine (unpubl. obs.…”
Section: Halurus Equisetifoliusmentioning
confidence: 99%
See 2 more Smart Citations
“…If it were at 13 °C August isotherm (a growth and/or reproduction limit) then H. equisetifolius would be expected in the North Sea south to the 13 °C August isotherm. In Ardr~ (1970Ardr~ ( , 1971, Dangeexd (1949), Donze (1968), Feldmann (1954, Gayral (1958), Giaccone & Longo (1976), Guiry (1978), den Hartog (1959), van den Hoek (1982a), van den Hoek & Donze (1966, 1967, Lawson & John (1977), Meunier (1965), Newton (1931), Norton (1970), Norton & Powel] (1979), Parke & Dixon (1976), Perez-Cirera (1975a), Prud'homme van Reine (unpubl. obs.…”
Section: Halurus Equisetifoliusmentioning
confidence: 99%
“…1. Distribution data on C. laciniata from the following sources: Ardr~ (1970Ardr~ ( , 1971, Cinelli et al (1979), Conde (1984), Cormaci 8, Furnari (1979), Cullinane & Whelan (1983), Dangeard (1949), Donze (1968), Egan (1983), Feldmann (1943, 1954, Gayral (1958), Giaccone (1978), Giaccone & Longo (1976), Guiry (1978), van den Hoek (1982a), van den Hoek & Donze (1966, 1967, Irvine, D. (1982), Irvine, L. (1983), Kain (1982), Levring (1974}, Maggs et al (1983, Norton (1976), Norton & Powell (1979), Parke & Dixon, (1976), Perez-Cirera (1975a, 1975b, Rueness (1977), Russell (1961Russell ( -1962, Russell (1968), Tittley et at. (1976) expected on the Danish coasts and on Helgoland, where summer temperatures arise above 11 °C.…”
Section: Callophyllis Laciniatamentioning
confidence: 99%
See 1 more Smart Citation
“…After years of uncertainty as to its rank (see Kylin, 1907Kylin, , 1944Kylin, , I946, 1949, Kornmann (1961) equated P. umbilicalis f. ]aciniata with P. purpurea, basing his interpretation of the latter name on specimens identified by early nineteenth century authorities in the absence of type material. Later check-lists followed Kommann, substituting P. purpurea for P. umbilicatis f. Iaciniata (Parke & Dixon, 1964, 1968, 1976South & Tittley, 1986). It should be noted that he observed that the species was Correspondence to: J. Brodie.…”
Section: Introductionmentioning
confidence: 99%
“…Canopies have been experimentally removed in the Fucus serratus, Laminaria digitata and L. hyperborea zones on the same Manx shore. Algae are named in accordance with the most recent U. K. check list (Parke and Dixon 1976) and animal nomenclature follows the Marine Fauna of the Isle of Man (Bruce et ai 1963). Encrusting calcareous algae, commonly referred to as "lithothamnia", are collectively termed "encrusting corallines".…”
Section: Introductionmentioning
confidence: 99%